Analyzing morphological changings of Tophane district after land fillings with using space syntax method - Ardicoglu, Ruya; Uslu, Aysel (Yildiz Technical Univ, Fac Architecture, 2022)
The starting point of the study is the argument that transformation of urban morphology because of production of places on coasts with landfilling. With landfilling on coasts, cities provide land acquisition. However, it causes changes in the morphological pattern of both coasts and cities. Therefore, landfilling is handled as one of the factors that caused the transformation of urban morphology. Istanbul Tophane coast, which was reshaped four times with coastal fillings, was chosen as the study area and the main material of the study for researching the spatial effects of the landfill. While landfilling provide new spatial formations on Tophane coasts, on the other hand, it causes changes in the morphological structure of the city and the coast. It is aimed to determine the influences of the filled coastal areas on urban morphology by researching and comparing the morphological changes of Tophane after each coastal filling. As the study method, Space Syntax, a spatial analysis method that provides an evaluation of the space in terms of usage practices and user perception along with physical analysis, was used. Each spatial change after landfilling in the Tophane coast was analysed with the Space Syntax method, and those changes are compared to each other. Space syntax analyses were done for the periods after 1743, 1894 and 1955 coastal fillings. It is aimed to analyse solid-void, axial and spatial arrangements after each coastal filling and target to evaluate the effects of morphological changes on spatial use and legibility of the coast. From the analyses, layout plan, axial connections, accessibility, the level of integration of the coast with its environment, quantitative findings of user movements and legibility of the places were obtained. As a result of the study, filling areas on coasts reshaped the urban morphology. It also causes new physical formations and differentiation in the usage practices of the coast and the legibility of the coastal area because of the changes in the morphological patterns. After each coast filling, a new morphological pattern formed that had an impact on the layout plan of the area, shoreline and arrangement of places. The layout plan developed in regular patterns after each filling. A linear axis has been developed in the plans and a circulation system has been developed where the deviations in pedestrian movements are reduced. It gives the result that the in-filled areas form a base for the formation of linear city plans and urban developments close to the grid plan order. By creating topographically flat areas on the coast and producing generally straight coastlines instead of the recessed natural coastline, the plan structure in cities and coastal areas can turn into a grid plan. It has been determined that the changes in urban morphology also cause changes in the legibility of the coast. The spatial arrangement in the physical formation and building densities are the determining parameters on the legibility of the space. In this study, the findings support the argument that the coastal fill was considered a factor in urban morphology transformation. With each filling application, changes are evaluated in the plan structures, functional uses, axial pattern, building densities and legibility of the coastline. Findings indicate that the density and arrangement of buildings in the filled areas are the determining issues on the city-coast relation, accessibility and the legibility of the coast, which are related to the solid-void pattern. Furthermore, researches on landfilling on coasts provide findings for planning and design processes along with the analysis of morphological changes. These findings are data that will contribute to the coastal planning, urban design and development processes of the city. In these kinds of studies, the space syntax is a beneficial method to be used both in the analysis of the existing morphological pattern and also for the pre-evaluation of the interventions planned to be implemented in the future from different perspectives. By evaluating morphological features with space syntax, findings related to past, current and future plans can be analysed. The studies conducted in the field of urban morphology considered the coastal landfills as a factor that changes the urban morphology. Hence, researching processes, actors and results of this factor are significant both in contributing to the planning and design processes and also in researching the transformation of urban spaces from history to the present.
Keywords: Urban morphology; land filling; space syntax; spatial change; Tophane